2013
DOI: 10.1016/j.aap.2013.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Inexperience and risky decisions of young adolescents, as pedestrians and cyclists, in interactions with lorries, and the effects of competency versus awareness education

Abstract: Published as:Twisk, D., Vlakveld, W., Mesken, J., Shope, J.T., Kok, G., 2013. Inexperience and risky decisions of young adolescents, as pedestrians and cyclists, in interactions with lorries, and the effects of competency versus awareness education. Accident Analysis and Prevention, 55, 219-225. Doi 10.1016/j.aap.2013

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…One contributing factor may be related to exposure and supervision. As children grow into adolescence, they behave with greater independence and may be exposed frequently to traffic situations, often unsupervised, but without fully-developed skills to engage in traffic [910]. Second, adolescents have a proclivity toward risk-taking tendencies that may lead to injury because adolescent traffic injuries are correlated with risk behaviours on the road [21112].…”
Section: Introductionmentioning
confidence: 99%
“…One contributing factor may be related to exposure and supervision. As children grow into adolescence, they behave with greater independence and may be exposed frequently to traffic situations, often unsupervised, but without fully-developed skills to engage in traffic [910]. Second, adolescents have a proclivity toward risk-taking tendencies that may lead to injury because adolescent traffic injuries are correlated with risk behaviours on the road [21112].…”
Section: Introductionmentioning
confidence: 99%
“…Several risk factors were identified within the reviewed non-accident studies. These related to road users are young age, as adolescent cyclists have difficulties practicing safe performance in blind spot areas near trucks [37], bbehavioural adaptation to safety measures [34], combination of factors affecting the likelihood of driver errors [18], cyclists' behaviour not conforming to normal expectations [18], driving in unfamiliar locations [18], gender (female cyclists might not correctly differentiate between the risks associated with inside and outside overtaking of trucks compared to male cyclists) [35], reaction time (slower reaction of drivers to objects visible only in mirrors compared to direct viewing through the front windscreen) [39] and time pressure related to delivery time slots for truck drivers [18]. These related to infrastructure are insufficient layout of loading area [40], lack of recognizable and comprehensible intersection design [32], narrow roads and tight corners [18], unseparated signalling phases for turning trucks and straight riding cyclists, particularly when traffic volumes and speeds are high [32] and specific configuration of bicycle lane and parking lane [36].…”
Section: Risk Factorsmentioning
confidence: 99%
“…At the same time, behavioural studies may highlight a phenomenon not seen in accident studies. For example, adult cyclists are the group most frequently involved in TCA [33], while a behavioural study found that young adolescent cyclists have difficulties in dealing with blind spot areas around trucks and could therefore be a suitable target group for receiving some kind of educational measures [37].…”
Section: Non-accident Analysismentioning
confidence: 99%
“…Given the low frequency of crashes and the asymmetrical relationship with risk behaviour (Hauer, 2008), this predictive power is rather strong, and supports the validity of self-reported risk behaviours as surrogate criteria for RSE programme outcomes, especially for those risk behaviours that strongly vary by subpopulations and by contextual factors such as the presence of peers and trip conditions. In contrast, if an RSE programme focuses on specific competencies and skills, such as road crossing (Duperrex et al, 2009) or interactions with trucks (Twisk, Vlakveld, Mesken, et al, 2013), observation of small samples of participants performing strictly defined tasks may provide reliable estimates of skill acquisition.…”
Section: Observation Of Behaviour Versus Self-reportmentioning
confidence: 99%
“…Frequently, actions need to be taken within an extremely small amount of time and space (Endsley, 1995), putting extra demands on the road user's information processing capacities. Because of these high demands, car drivers, for instance, can only acquire these skills after extensive practice (Twisk, Vlakveld, Mesken, et al, 2013). Moreover, the more complex a task is (for instance, left turns in busy traffic), the more hours of practice are required before behaviour becomes sufficiently safe.…”
Section: Mobility Inexperience and The Complexity Of The Road Taskmentioning
confidence: 99%